Nitrification inhibitor addition to farm dairy effluent to reduce nitrous oxide emissions - Cosentino, Vanina Rosa Noemi; Romaniuk, Romina Ingrid; Mortola, Natalia Andrea; Otero Estrada, Edit; Martinek, Nicole; Beltran, Marcelo Javier; Costantini, Alejandro Oscar; Imhoff, Silvia; Taboada, Miguel Angel (Sociedade Brasileira de Ciência do Solo, 2024)
Increasing the use of nitrogen (N) fertilizers will be necessary to enhance grain and pasture yields to satisfy the growing world demand for food. Organic amendments, such as farm dairy effluents (FDE), are an alternative to traditional synthetic fertilizers. However, part of the applied N could be lost as ammonia (NH3) volatilization or nitrous oxide (N2O) emission, decreasing N availability to plants. Nitrification inhibitors, such as dicyandiamide (DCD), suppress the microbial process of nitrification, decreasing soil nitrate concentration and, therefore, N2O emission. Reducing N2O losses from agricultural soils is a key subject for sustainable production. This research aimed to quantify the effect of DCD addition to the FDE on the emissions of N 2O and the volatilization of NH3 from the soil. A field trial was carried out in which NH 3 volatilization and N2O emission were measured over 49 days after applying FDE, FDE with DCD (DCD), and control (C, without N added) treatments. The amount of N applied as FDE was 120 kg of N ha-1. Accumulated N2O emission during the 49 days after the application was 526, 237, and 174 g N2O-N ha-1 from the soil in the FDE, DCD, and C treatments, respectively. No significant differences were observed in accumulated NH3 volatilization. Pasture yield was higher in DCD treatment, followed by C and FDE. Under low temperatures and high soil moisture conditions, adding DCD to the FDE could be considered an effective alternative to increase pasture yields, decrease N2O emissions, and maintain NH3 volatilization, reducing total N losses to the atmosphere by about 14 %. Adding DCD to the FDE is a promising alternative for the more efficient N use of farm dairy effluents as fertilizer to mitigate N losses, tending to reduce N losses as N2O emissions. More studies are necessary to verify the result of using FDE + DCD under different soils and climates.